2022
DOI: 10.1088/1748-9326/ac7e5f
|View full text |Cite
|
Sign up to set email alerts
|

Higher landscape diversity associated with improved crop production resilience in Kansas-USA

Abstract: Cropland expansion and agriculture intensification have been the primary methods to increase food production since the 19th century. The resulting landscape simplification, however, can impede long-term agricultural crop productivity. This paper examines the role of landscape diversification on resilience of corn, soy, and winter wheat production, in terms of crop yield and yield variability, in the state of Kansas. The study uses panel data analysis with county fixed effects and time trends to estimate the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…A stable and resilient crop production enterprise maintains similar outcome despite year‐to‐year climate and resource variability (Nelson et al., 2022). In the late 1800s and early 1900s, open‐pollinated corn hybrids showed up to a maximum of ±1.6 Mg ha −1 corn yield variability from one year to another.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A stable and resilient crop production enterprise maintains similar outcome despite year‐to‐year climate and resource variability (Nelson et al., 2022). In the late 1800s and early 1900s, open‐pollinated corn hybrids showed up to a maximum of ±1.6 Mg ha −1 corn yield variability from one year to another.…”
Section: Resultsmentioning
confidence: 99%
“…The increased variability is largely a function of higher yield over time with consequently greater magnitude of potential loses with yield declines being possible "down to zero." A stable and resilient crop production enterprise maintains similar outcome despite year-to-year climate and resource variability (Nelson et al, 2022). In the late 1800s and early 1900s, open-pollinated corn hybrids showed up to a maximum of ±1.6 Mg ha −1 corn yield variability from one year to another.…”
Section: Corn Yield Variabilitymentioning
confidence: 96%
“…Given that many of these HD-HP counties will experience significant shifts in climate conditions over the next century (Burchfield, 2022), opening up possibilities for diversification in landscapes with particularly favorable cultivation conditions could support climate-smart transitions and boost agricultural resilience (Hertel et al, 2021). Higher levels of diversity in cropping systems have the potential to improve crop yields and mitigate the effects of extreme weather conditions leading to greater yield stability (Redhead et al, 2020;Nelson et al, 2022). Moreover, crop diversity provides greater stability of total food and nutrition supply (Renard and Tilman, 2019) and economic value (Birthal and Hazrana, 2019;Sánchez et al, 2022) as crops responses to extreme weather conditions and changes in climate vary (Elmqvist et al, 2003).…”
Section: Finding : Biophysical Conditions Bound Diversity-productivit...mentioning
confidence: 99%
“…First, field-scale research suggests that increased crop diversity may reduce the need for chemical inputs (Redlich et al, 2018;Thomine et al, 2022), supporting ecosystem health while also reducing on-farm expenses. Relatedly, agricultural experiments and landscape-scale studies suggest that increasing crop diversity and natural habitat near crop fields are associated with higher crop yields (Smith et al, 2008;Grab et al, 2018;Burchfield et al, 2019;Dainese et al, 2019;Galpern et al, 2020;Garland et al, 2021) and increased yield stability (Redhead et al, 2020;Nelson et al, 2022). More diverse agricultural landscapes are also associated with higher financial returns (Sánchez et al, 2022), reduced farm economic volatility (Abson et al, 2013), and more stable national food supplies (Renard and Tilman, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been found that higher landscape diversity mitigates the impact of extreme weather conditions on crop yields. Consequently, the yields of winter wheat, corn and soybean have increased in to varying degrees (Nelson et al 2022). Landscape diversity has an impact on animal richness.…”
Section: Introductionmentioning
confidence: 99%